Control de Burkholderia glumae en el cultivo de Arroz (Oryza sativa L.) utilizando 02 productos de acción Bactericida, en la E.E.A El Porvenir – San Martin - Martínez Guevara, Nicanor (2016)
This research work had as objectives to determine the most efficient treatment of management for the prevention and control of the bacterium Burkholderia glumae agent causal of the panicle of rice bacterial blight, to evaluate the influence of the management treatments applied in different doses (Green Star and Oxilobac) and stages, on the productivity of rice variety INIA-509 "La Esperanza" and determine the relation benefit - cost of the evaluated treatments of rice cultivation. We conducted this research in the experimental area of the National Program of rice - E.E.A. "El Porvenir" - INIA, San Martin Region. We used the Randomized Complete Block Design (RCBD) with 4 replications and 14 treatments; with a total of 56 experimental units. Field data is stored and analyzed in the SPSS software v. 20, the data were subjected to the Tukey test with a significance level of <0,05. We obtained as a result to the most efficient treatment of management, for the prevention and control of the bacterium Burkholderia glumae, to T9 (0.29%) where low was reported the incidence of the bacteria. However, in the investigation the higher incidence of the bacteria cannot exceed 0.5 %, case of the T14 (0.44 %). This event was due to the non- favorable climatic conditions to the development of the bacteria in the flowering stage (July). Given this problem to control bacteria t is recommended to apply the treatment nine accompanied by an integrated management